Suppressive effects of black seed oil on ovalbumin induced acute lung remodelling in E3 rats (Swiss Medical Weekly, 2010)
OBJECTIVE: Black seed oil (BSO) is widely used as a traditional medicine for asthma and other inflammatory diseases. The aim of this study is to evaluate the effects of BSO on ovalbumin (OVA) induced acute lung remodelling in E3 inbred rats. METHOD:Rats were divided into three groups; Control, OVA and BSO. The rats were intraperitoneally sensitised and challenged intranasally with OVA and treated intraperitoneally with pure BSO for seven days. The collagen deposition and other pathological alteration were determined by Masson’s trichrome, PAS and HE staining. Activity of arginase, ornithine decarboxylase (ODC) and proline level was determined by spectrophotometry, and polyamine by HPLC. The mRNA expression of arginase І, endothelin1 (Edn1), matrix metallopeptidase 3 (MMP3) and growth factors was determined by real time RT-PCR. RESULTS: Massive inflammation and characteristics of lung remodelling including collagen deposition, goblet cell hyperplasia and proline level were observed in the lungs of OVA exposed rats. Administration of BSO in the OVA exposed rats suppressed the inflammatory cells infiltration, goblet cell hyperplasia and collagen deposition. The activity of total arginase and ODC; proline and polyamine level was decreased in the lung homogenate of BSO treated rats. Furthermore, BSO abrogated the mRNA expression of Edn1, MMP3, transforming growth factor beta (TGF-β), fibroblast growth factor 2 (FGF2) and vascular epidermal growth factor (VEGF) in the lungs of OVA challenged rats. CONCLUSION: Administration of BSO significantly reduced the level of allergen induced lung remodelling. The effect of BSO on lung remodelling is probably mediated by the inhibition of arginase pathways and the expression of Edn1, MMP3 and growth factors. Our findings suggest that BSO might have useful implications in the treatment and future research into allergen-induced lung remodelling.